A STUDY ON WHAT FACTORS IN FACEBOOK MEDIA CONTENT RELATED TO SEX EDUCATION WILL ATTRACT USERS (Proceedings of the World Conference on Media and Mass Communication, 2023)
Social media is being used by more and more people to share and educate themselves on gender-related and sex-education-related topics. There is a large amount of research on the subject of sex education on Facebook and its impact on users, but such study in Vietnam’s context is still rare. The purpose of this study is to identify elements in Facebook media content connected to sex education that may appeal to Vietnamese users. We use persuasion theory, which offers characteristics that are employed when people have a desire to convince others and effectively communicate their message to readers and listeners, to accomplish that goal. In this study, a mixed methodology is used to gather and analyze data. First, we selected the Ushare - Wecare Facebook page, which was created by a group of University of Foreign Languages - Hanoi National University students, as one of the Facebook pages that disseminates information about Sex Education. By counting the number of times Ethos, Pathos, and Logos appeared in the posts we selected, content analysis may be used to determine how readers are drawn to material through the interaction of each post. According to the findings of our study, all three elements—ethos, logos, and pathos—are utilized in media content that deals with sex education, with logos and pathos being most frequently used in posts. As a result of our research, communicators can use data to create media material that is both engaging for consumers and imparts the necessary knowledge about sex education.
Keywords: Facebook, media content, sex education, user engagement, Vietnam